2001
DOI: 10.1006/jmsc.2001.1130
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between schools, clusters of schools, and abundance in pelagic fish stocks

Abstract: Small pelagic fish are known to aggregate into schools and clusters of schools. It is commonly assumed that the number of such schools and clusters, as well as their size and densities, will vary with the stock abundance. We have carried out a PCA based meta-analysis, using series of acoustic survey data from five different locations in Europe to examine this assumption. The study concluded that there was no discernible relationship between stock abundance and the number of schools seen, or on the clustering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 20 publications
1
43
0
4
Order By: Relevance
“…The 'echo integration by shoal' process was employed (Scalabrin & Massé 1993, Petitgas et al 2001, Guillard et al 2004), which did not take into consideration the individual fish but rather the structure of fish schools, employing the echo types defined above. Graphical measure corrections on fish schools were carried out according to Johannesson & Losse (1977).…”
Section: Methodsmentioning
confidence: 99%
“…The 'echo integration by shoal' process was employed (Scalabrin & Massé 1993, Petitgas et al 2001, Guillard et al 2004), which did not take into consideration the individual fish but rather the structure of fish schools, employing the echo types defined above. Graphical measure corrections on fish schools were carried out according to Johannesson & Losse (1977).…”
Section: Methodsmentioning
confidence: 99%
“…To test different environmental conditions in consecutive years, the years 2001 to 2003 were chosen after the analysis of satellite data spanning two decades, the 1990's and 2000's. The data sets revealed that 2001 was an exceptionally warm year, particularly in summer, with strong stratification mainly because of reduced wind stress in the winter of -2001(McQuatters-Gollop et al, 2008Buongiorno Nardelli et al, 2010). The year 2002 was average in terms of temperature distribution and 2003 was remarkably cold when compared to the mean conditions, with significantly higher wind stress (McQuatters-Gollop et al, 2008).…”
Section: Design Of Simulationsmentioning
confidence: 99%
“…Georgia's fishing fleet is much smaller (CastillaEspino et al, 2014) and Georgian fishery enterprises hire a limited number of Turkish purse seiners each year. The fact that anchovy aggregate to form dense schools when overwintering makes them specifically vulnerable to exploitation and potential overexploitation (Auckland and Reid, 1998;Petitgas et al, 2001). …”
Section: An Overview Of the Black Sea Anchovy Fishery Characteristicsmentioning
confidence: 99%
“…These species form either pure or mixed schools (Bakun & Cury 1999) and may adjust their spatial extension to maintain constant density within schools (Petitgas et al 2001). The organization of schools into clusters has already been described for many stocks (Freon & Misund 1999, Petitgas et al 2001 and references therein), and is probably related to the patchiness of the environment (Schneider 1989, Swartzman 1991. Within a cluster of schools the spatial distribution can be very heterogeneous.…”
Section: Introductionmentioning
confidence: 94%